Water and Roman urbanism : towns, waterscapes, land transformation and experience in Roman Britain - Rogers, Adam, 1981- (Mnemosyne, Supplements, 2013)
Water and Roman Urbanism: Towns, Waterscapes, Land Transformation and Experience in Roman Britain offers a new perspective for investigating Roman settlement and how urban spaces were created and experienced by focusing on the relationship between settlement and water and the meanings attributed to these places. Rather than a descriptive approach to the urban fabric it emphasises social context and cultural meaning through interpretative frameworks of analysis. Central are the cultural and experiential implications of water forming part of towns, rather than economic and practical arguments, and the way in which these places were used and altered over time. The book emphasises a social approach and has considerable implications for our understanding of life in the Roman period as a whole.